2010
DOI: 10.1007/s00334-010-0243-5
|View full text |Cite
|
Sign up to set email alerts
|

A new Late-glacial and Holocene record of vegetation and fire history from Lago del Greppo, northern Apennines, Italy

Abstract: Detailed Late-glacial and Holocene palaeoenvironmental records from the northern Apennines with a robust chronology are still rare, though the region has been regarded as a main area of potential refugia of important trees such as Picea abies and Abies alba. We present a new high-resolution pollen and stomata record from Lago del Greppo (1,442 m a.s.l., Pistoia, northern Apennines) that has been dated relying on 12 terrestrial plant macrofossils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 57 publications
(94 reference statements)
7
57
0
5
Order By: Relevance
“…NER has an allelic and haplotype richness 16% and 54% higher, on average, than much larger and less isolated Alpine populations. This suggests that the northernmost part of the Apennine distribution is the most likely refugial area or, at least, the area where silver fir was most abundant during the Last Glacial Maximum (LGM): a hypothesis that fits well with palaeobotanical data (Vescovi et al ., ; Magri et al ., ). Besides its conservation relevance, the correct location of refugial populations can help solve the long‐lasting problem of accurately calculating historical migration rates (Cheddadi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…NER has an allelic and haplotype richness 16% and 54% higher, on average, than much larger and less isolated Alpine populations. This suggests that the northernmost part of the Apennine distribution is the most likely refugial area or, at least, the area where silver fir was most abundant during the Last Glacial Maximum (LGM): a hypothesis that fits well with palaeobotanical data (Vescovi et al ., ; Magri et al ., ). Besides its conservation relevance, the correct location of refugial populations can help solve the long‐lasting problem of accurately calculating historical migration rates (Cheddadi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…; Vescovi et al, 2010) in the northern Apennines is clearly excluded and therefore suggests a distinct pattern for the Abies spread in this area. Altitudinal abundance reflects the ecological optimum of trees so that tree migration was faster at optimum elevation and slower at lower and higher elevations, rather than exhibiting a linear relationship with elevation (van der Knaap et al, 2005).…”
Section: Abies Immigrationmentioning
confidence: 93%
“…From c. 3,600 cal BP onward, Olea curves increase in Lago Alimini Piccolo and Lago di Pergusa (c. 20% in both sites), but also increasing in Lago Battaglia at c. 3,100 and 2,600 cal BP. Similarly, in central Italy, some off-site cores show the occurrence of Olea during the early Holocene (Lago dell'Accesa in Tuscany: DrescherSchneider et al, 2007), with its continuous presence from c. 7,300 to 7,000 cal BP also at Lago del Greppo (Vescovi et al, 2010). In Tuscany, at Lago di Massaciuccoli (Mariotti Lippi et al, 2007), Olea pollen is present in traces amounts, and found only in the layers dating to the Roman Age; also elsewhere in the region, Olea was discontinuously recorded in low amount (Mariotti Lippi et al, 2015;Mariotti Lippi in verbis).…”
Section: (T IV T V)mentioning
confidence: 99%